Nutrition Education in The Prevention of Acute Kidney Failure in Adolescents - Musniati, Nia; Sari, Mega Puspa; Aini, Rahmatika Nur; Nurjanah, Erni; Siregar, Dahliana; Rahayu, Iga (Universitas Padjadjaran, 2024)
PKidney disease is the 10th cause of death in Indonesia, namely 42,000 per year. Most of the causes of kidney disease are hypertension, diabetes and kidney inflammation. Teenagers have risky snacking behavior, namely snacks that are high in sugar, salt and fat which affect nutritional status and become a risk factor for non-communicable diseases in the future. The partner of this activity is SMA Muhammadiyah 13 Jakarta. Based on the initial study, it was found that most of the knowledge of adolescent nutrition at SMA Muhammadiyah 13 was in the unfavorable category (53.5%). The target of this activity is students who are registered at partner institutions as many as 30 students. The purpose of this community service is to increase youth's knowledge in preventing kidney disease such as consuming healthy snacks and good eating patterns by conducting nutrition education. This activity consists of 3 stages, namely the planning stage, the implementation stage, and the evaluation stage. Implementation of activities consists of education and practice. The implementation of the activity was February 3, 2023. The evaluation results showed that there was an increase in the average before and after education, namely 8.03 to 9.73. The results of the statistical test showed that there was a significant difference/effect of education on students' knowledge with p=0.000. There is an increase in students' knowledge about the prevention of acute kidney failure by providing nutrition education. Students are expected to be able to apply a balanced nutritional diet to prevent suffering from kidney failure in the future.Keywords: Nutrition education, youth, kidney disease.